2021
DOI: 10.1371/journal.pone.0257761
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass habitat suitability model for Redang Marine Park using multibeam echosounder data: Testing different spatial resolutions and analysis window sizes

Abstract: Integrating Multibeam Echosounder (MBES) data (bathymetry and backscatter) and underwater video technology allows scientists to study marine habitats. However, use of such data in modeling suitable seagrass habitats in Malaysian coastal waters is still limited. This study tested multiple spatial resolutions (1 and 50 m) and analysis window sizes (3 × 3, 9 × 9, and 21 × 21 cells) probably suitable for seagrass-habitat relationships in Redang Marine Park, Terengganu, Malaysia. A maximum entropy algorithm was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 130 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…In Malaysian coastal waters, an acoustic dataset from a multibeam echosounder and species occurrence data were used to model suitable seagrass habitats. This study found that the bathymetry data was the most influential predictor (Muhamad et al, 2021) when simply focusing on coastal areas and only evaluating reduced current and wave action as factors. This study, however, evaluated a more comprehensive set of factors to obtain more pertinent and helpful data to map habitat suitability and inform effective transplantation efforts.…”
Section: Applicability To Decision-makingmentioning
confidence: 85%
“…In Malaysian coastal waters, an acoustic dataset from a multibeam echosounder and species occurrence data were used to model suitable seagrass habitats. This study found that the bathymetry data was the most influential predictor (Muhamad et al, 2021) when simply focusing on coastal areas and only evaluating reduced current and wave action as factors. This study, however, evaluated a more comprehensive set of factors to obtain more pertinent and helpful data to map habitat suitability and inform effective transplantation efforts.…”
Section: Applicability To Decision-makingmentioning
confidence: 85%